Peran Vitamin D Hasil Sintesis Kuliot terhadap Kekuatan Tulang dalam Hubungan Sistem Muskuloskeletal dan Integumen - Denisya Risqi Amelia; Arya Listyo Adi; Nabila Fredlina M; Claudia Aulia; Fernanda Della; Danian Pasha Pratama; Liss Dyah Dewi Arini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Vitamin D is a vital nutrient primarily produced through skin exposure to UVB rays. Vitamin D plays a crucial role in maintaining healthy bones and the musculoskeletal system. The skin, as the organ that produces vitamin D, works closely with the musculoskeletal system to maintain bone strength and function. This article explains the synthesis, metabolism, and action of vitamin D, as well as its impact on bone strength and the relationship between the two systems in supporting human body function. Recent studies fully explain the importance of a balance between adequate sunlight exposure and vitamin D metabolism for maintaining bone and muscle health.